Emergent universal critical behavior of the 2D N-color Ashkin-Teller model in the presence of correlated disorder - Dudka, M.; Fedorenko, A.A. (Condensed Matter Physics, 2017)
We study the critical behavior of the 2D N-color Ashkin-Teller model in the presence of random bond disorder
whose correlations decays with the distance r as a power-law r
−a
. We consider the case when the spins of
different colors sitting at the same site are coupled by the same bond and map this problem onto the 2D system
of N/2 flavors of interacting Dirac fermions in the presence of correlated disorder. Using renormalization group
we show that for N = 2, a “weakly universal” scaling behavior at the continuous transition becomes universal
with new critical exponents. For N > 2, the first-order phase transition is rounded by the correlated disorder
and turns into a continuous one. Ми вивчаємо критичну поведiнку 2D N-кольорової моделi Ашкiна-Телера у присутностi безладу типу випадкових зв’язкiв, кореляцiї якого спадають з вiдстанню r за степеневим законом r
−a
. Ми розглядаємо
випадок, коли спiни рiзних кольорiв, що сидять на тому ж самому вузлi, зв’язанi одним зв’язком, i переводимо цю задачу на 2D систему N/2 ароматiв взаємодiючих фермiонiв Дiрака у присутностi скорельованого безладу. Використовуючи ренорм-групу, ми показуємо, що для випадку N = 2 “слабка унiверсальнiсть”
при неперервному переходi стає унiверсальною з новими критичними показниками. Для N > 2 фазовий
перехiд першого роду перетворюється скорельованим безладом в неперервний.